Nutrient resources and stoichiometry affect the ecology of above- and belowground invertebrate consumers - Jonas, Jayne (Kansas State University, 2007)
Aboveground and belowground food webs are linked by plants, but their reciprocal influences are seldom studied. Because phosphorus (P) is the primary nutrient associated with arbuscular mycorrhizal (AM) symbiosis, and evidence suggests it may be more limiting than nitrogen (N) for some insect herbivores, assessing carbon (C):N:P stoichiometry will enhance my ability to discern trophic interactions. The objective of this research was to investigate functional linkages between aboveground and belowground invertebrate populations and communities and to identify potential mechanisms regulating these interactions using a C:N:P stoichiometric framework. Specifically, I examine (1) long-term grasshopper community responses to three large-scale drivers of grassland ecosystem dynamics, (2) food selection by the mixed-feeding grasshopper Melanoplus bivittatus, (3) the mechanisms for nutrient regulation by M. bivittatus, (4) food selection by fungivorous Collembola, and (5) the effects of C:N:P on invertebrate community composition and aboveground-belowground food web linkages. In my analysis of grasshopper community responses to fire, bison grazing, and weather over 25 years, I found that all three drivers affected grasshopper community dynamics, most likely acting indirectly through effects on plant community structure, composition and nutritional quality. In a field study, the diet of M. bivittatus was dominated by forbs with grasses constituting only a minor fraction of their diet under ambient soil conditions, but grass consumption approximately doubled as a result of changes in grass C:N:P. M. bivittatus was found to rely primarily on selective consumption of foods with varying nutritional quality, rather than compensatory feeding or altering post-ingestive processes, to maintain C:N homeostasis in a laboratory experiment. In a soil-based mesocosm study, I show that Collembola feed on both saprophytic and AM fungi, in some cases exhibiting a slight preference for AM fungi. In the final study, although I did not find the expected indirect relationship between soil Collembola and aboveground herbivory as mediated through host plant quality, there were significant effects of root C:N and AM colonization on Collembola density and of plant C:N on aboveground herbivory. Overall, this research shows that host plant C:N:P stoichiometry can influence both above- and belowground invertebrate population, community, and food web dynamics.
Keywords: Grasshoppers; Collembola; Stoichiometry; Food web; Grassland; Biology, Ecology (0329)